The protein C deficiency and its effects on in-vitro fertilization outcome and recurrent pregnancy loss: a Syrian cohort study - Khoury, Fadi; Deeb, Haya; Jarouj, Rana; Khoury, Hanna; Alhalabi, Nawras; Alhalabi, Marwan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Protein C deficiency is a rare disease; it could be primary or secondary. Female patients with protein C deficiency may develop pregnancy-associated thrombosis. The clear association between the protein C deficiency and fertility or in-vitro fertilization (IVF) results has not been known yet. In our study, we aimed to determine the prevalence of protein C deficiency in Syrian infertile women and to assess the impact of protein C deficiency on abortion, recurrent IVF Failure, and IVF results. Methods: the electronic patients’ results were retrospectively screened. A total of 238 women, who had IVF cycles between January 2012 and December 2017 in a tertiary care hospital, met our including criteria. Results: the prevalence of protein C deficiency was 13.45%. There was a significant association between the protein C level and recurrent pregnancy loss (RPL). Furthermore, the protein C deficiency has an impact on the IVF results. Additionally, we did not find any association between protein C deficiency and age or number of previous IVF cycles. Conclusions: the protein C could be the hidden factor that affects IVF results. More research should be done to better understanding the role of protein C in infertility and IVF.